IBERO-AMERICAN THINKING: THE PATHWAY TO INTERNATIONALIZATION - Vargas, Thais Conte [UNESP]; Cunha, Maira Darido da (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2020)
The analysis here presented seeks to bring forth the recent trajectory of a group of researchers who have dedicated themselves to the systematic study of Ibero-American Education. Although hundreds of research papers are being written on the same theme, the research group Cervantes was born, in 2006, due to the cooperation agreement between the Sao Paulo State University and the University of Alcala de Henares, in order to offer a knowledge exchange between the two institutions. The impacts of new technologies and the growth of the group caused an intense change in the dynamics of the participants' performance and in the way, researchers started to produce and disseminate the scientific contributions elaborated. As of 2012, the internationalization actions were strengthened: other Latin American universities joined the group and there was a profound restructuring of the Ibero American Journal of Education Studies. In 2014, all intellectual production was made available in digital format.
Keywords: Education; Ibero-America; Internationalization; Scientific divulgation